Adolescent internet use predicts higher levels of generalized and social anxiety symptoms for girls but not boys - Gabriel A. Tiraboschi; Gabrielle Garon-Carrier; Jonathan Smith; Caroline Fitzpatrick (Preventive Medicine Reports, 2023)
Past research suggests that internet use can increase the risks of internalizing symptoms in adolescents. However, bidirectional relationships between adolescent internet use and anxiety symptoms have received very little attention. Furthermore, few studies have examined these links according to sex. The present study attempts to fill this gap by investigating longitudinal associations between Canadian boys’ and girls’ internet use and symptoms of generalized anxiety and social anxiety using data from the Quebec longitudinal Study of Child Development. A sample of 1324 adolescents (698 girls, 626 boys) self-reported the number of hours per week they spent on the internet and their symptoms of generalized and social anxiety at ages 15 and 17. We estimated two cross-lagged panel models with social or generalized anxiety symptoms and internet use at age 15 predicting those same variables at age 17. Sex was used as a grouping variable and socioeconomic status was included as a control variable. Internet use at 15 predicted generalized and social anxiety symptoms at age 17 in girls, but not boys. Social and generalized anxiety symptoms at age 15 did not predict internet use at age 17 for both boys and girls. These results suggest that internet use can be a significant risk factor for the development of anxiety symptoms in adolescent girls. Girls may be more vulnerable to the negative effects of internet use due to increased sensitivity to social comparisons. Thus, helping girls develop healthier internet use habits should be a target for promoting their mental health.